Challenges and Strategies for Implementing Inclusive Curriculum in Elementary Schools - Ainiyah, Ziana Dhurrotul (Tarsib: Jurnal Program Studi PGMI, 2024)
This study aims to evaluate the challenges and strategies in implementing an inclusive curriculum at Elementary Sshool II Dasin. The methodology used in this study is a qualitative approach, with data collection techniques including interviews, observations, and document analysis. The subjects consist of ten teachers who have been involved in the implementation of the inclusive curriculum over the past two years. The findings indicate several challenges in implementing the curriculum. First, there is a lack of competent human resources, low involvement of parents and the community, and limited support from the school. The study also identifies strategies to effectively address these challenges, such as educator training, the establishment of an inclusion committee at the school, and increasing parental and community participation in the implementation of the inclusive curriculum.